مشكلات تعليم اللغة العربية في مناطق التداخل اللغوي في السودان - د. عوض أحمد أدروب (White Nile Journal for Studies and Research, 2014)
This research aims at identifying the problems of teaching Arabic language in the areas of linguistic interference in the Sudan. The importance of the research lies in the fact that it displays all the efforts that were exerted in the field of teaching and learning Arabic language in these regions As for the tools used to uncover these problems. the researcher used observation. questionnaire and interviews that were used in previous studies. The most important results of the research are that the learners of Arabic in linguistic interference regions face problems related to sounds, vocabulary items and structures of this language because they are not native speakers of Arabic. This happens although Arabic language is the language of instruction in schools. Based on these findings, the researchers recommends that Arabic language teaching should be facilitated and simplified to be taught to students in linguistic interference areas and teachers should be given special training to teach this language to Non-native speakers of Arabic It is also recommended that variation in linguistic background should be taken into account when designing Arabic language syllabus for multi-lingual states like the Sudan.